Aulas de educação física e os jogos escolares: reflexões sobre dois cenários - Santos, Marília Baldoino dos [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Since the 1950s the sport has gained prominence in Physical Education classes and established itself as hegemonic in the following decades, being greatly influenced by the performance sport. The School Games emerge with these references, establishing themselves as a space for exploration and diffusion of sport within the school culture. The perspective of the body culture of movement that circumscribed the pedagogical object of Physical Education at school brought new reflections to think about sport content, However, Physical Education classes and School Games usually take place in an ambiguous field between this new configuration and the sports tradition. In this sense, this study aimed to analyze the relationship between Physical Education classes and School Games in the perspectives of students. The research, based on the qualitative approach, was guided by a descriptive study. The collection was done through semi-structured interviews and systematic observation of the training sessions that were aimed at preparing a group of students for the School Games. The results pointed out that performance sports are still rooted in school, training and physical education classes were confounded within the school context and the participating and non-participating students expressed different perspectives regarding the School Games. The contents developed in training and Physical Education classes were practically the same. Students participating in the School Games did not present many elements for changes in the operationalization of such games, explaining an accommodation with the current model. The non-participants, in some moments, said that they felt excluded from the games, because they wanted to participate, but found obstacles to it. Among these non-participants, it was evidencing some misunderstanding about the dynamics and structure of the School Games.

Desde a década de 1950 o esporte tem ganhado relevo nas aulas de Educação Física e se estabelecendo como hegemônico nas décadas seguintes, sendo bastante influenciado pelo esporte de rendimento. Os Jogos Escolares surgem com estas referências, se estabelecendo como um espaço de exploração e difusão do esporte dentro da cultura escolar A perspectiva da cultura corporal de movimento que circunscreveu o objeto pedagógico da Educação Física na escola trouxe novas reflexões para se pensar o conteúdo esporte, porém, as aulas de Educação Física e os Jogos Escolares costumam se dar num campo ambíguo entre esta nova configuração e a tradição esportiva. Neste sentido, este estudo teve como objetivo analisar as relações das aulas de Educação Física com os Jogos Escolares nas perspectivas dos estudantes. A investigação, assentada na abordagem qualitativa, se pautou por um estudo descritivo. A coleta foi realizada por meio de entrevista semiestruturada e observação sistemática dos treinos que eram voltados para a preparação de um grupo de estudantes para os Jogos Escolares. Os resultados apontaram que o esporte de rendimento ainda está enraizado na escola, os treinos e as aulas de Educação Física se confundiam dentro do contexto escolar e os alunos participantes e não participantes manifestaram perspectivas distintas a respeito dos Jogos Escolares. Concluiu-se que os conteúdos desenvolvidos nos treinos e nas aulas de Educação Física eram praticamente os mesmos, os estudantes participantes dos Jogos Escolares não apresentaram muitos elementos para mudanças na operacionalização de tais jogos, explicitando uma acomodação com o modelo vigente, já os não participantes, em alguns momentos, disseram que se sentiam excluídos dos jogos, pois tinham vontade de participar, todavia encontravam empecilhos para isso, dentre estes não participantes... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Escolas - Exercicios e jogos; Educação fisica; Competição (Esporte); Sports